Design and evaluation of an image‐guidance system for robot‐assisted radical prostatectomy. (5th February 2013) - Thompson, Stephen; Penney, Graeme; Billia, Michele; Challacombe, Ben; Hawkes, David; Dasgupta, Prokar
Abstract : What's known on the subject? and What does the study add?: Systems for image guidance during laparoscopic surgery can be broadly defined as systems that enable the surgeon to refer to preoperatively gathered information during the procedure. For a laparoscopic system the preoperative information can be overlaid onto the laparoscopic video screen. Examples of surgical image‐guidance systems and the results of early testing are not uncommon but the technical methodologies used vary widely as do the visualisation methods. This study reports our experience of using an image‐guidance system on 13 patients. Furthermore, we use previously proposed methodology to form a development and evaluation framework specific to image‐guided laparoscopic radical prostatectomy. Finally, we propose that if the system development process is properly designed, it should be possible to correlate system technical parameters with clinical outcomes. We present a possible plot for the key technical parameter of accuracy. Better understanding of this correlation should enable robust development and evaluation of surgical image‐guidance systems to optimise patient outcomes. Objective: To implement and test the feasibility of an image‐guidance system for robot‐assisted radical prostatectomy (RARP). Laparoscopic surgical outcomes may be improved through image guidance. However, to demonstrate improved outcomes rigorous evaluation techniques are required. Therefore we also present our work in establishing robust evaluation techniques. Patients and Methods: Development work used three cadavers and an anatomy phantom. The system has been used on 13 patients. During surgery the surgeon can refer to the patient's magnetic resonance imaging (collected before the operation) overlaid on the endoscopic video image. The result of the overlay process was measured qualitatively by the surgeon with reference to the desired clinical outcomes. Results: The use of the overlay system has not resulted in any measurable change in clinical outcomes. The surgeons found the system to be a useful tool for reference during surgery. A more rigorous evaluation method is proposed that will enable on‐going development. Conclusion: Image guidance during RARP is feasible. We propose a series of measures that will improve further development and evaluation.